Game Education “Fruit Shooter” Berbasis Android - Paryanta - STMIK AUB Surakarta (Indonesian Journal of Networking and Security (IJNS), 2019)
Abstract - The development of Game Technology circulating in the community is mostly used by children for games that are less beneficial for children. Many parents feel anxious about their children who play games every day until they forget the time to study via their smartphone. Based on the problems faced by the parents above, the authors developed an educational and edutainment or Android-based educational game that is useful for children helping in their learning activities. Game development methods use the Waterfall method while game design uses storyboarding and Unified Modeling Language (UML), while this game is built using java programming language with Unity software. The results of this research have produced a game called "Fruit Shooter" with a two-dimensional (2D) display based on Android. This game is played by 1 person and has 3 levels of obstacles. The genre of this game is educational and edutainment games. Keywords: Android, two dimensions, educational, edutainment, Unity, Abstraksi - Perkembangan Teknologi Game yang beredar di masyarakat sebagian besar dimanfaatkan oleh anak-anak untuk permainan yang kurang bermanfaat bagi anak Banyak orang tua merasa resah terhadap anaknya yang setiap hari main game sampai lupa waktu untuk belajar melalui smartphone yang dimiliki. Berdasarkan permasalahan yang diahadapi para orang tua tersebut diatas penulis mengembangkan sebuah game bergenre educational and edutainment atau edukasi yang berbasis Android bermanfat untuk anak-anak membantu dalam kegiatan belajarnya. Metode pengembangan game menggunakan metode Waterfall sedangkan perancangan game menggunnakan storyboard dan Unified Modeling Language (UML), Sedangkan Game ini dibangun dengan menggunakan bahasa pemrogaman java dengan sofware Unity. Hasil penilitian ini telah menghasilkan game berjudul “Fruit Shooter” dengan tampilan Dua Dimensi (2D) berbasis Android. Game ini dimainkan oleh 1 orang dan mempunyai 3 level rintangan. Genre dari game ini adalah game educational and edutainment. Kata kunci : Android, dua dimensi, educational, edutainment, Unity,